A rare case of pulmonary lymphomatoid granulomatosis complicated with venous thrombosis - Maral, Senem; Albayrak, Murat; Öztürk, Hacer Berna Afacan; Incekara, Funda; Yıldız, Abdulkerim; Abayrak, Aynur; Kaya, Sadi (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2022)
Lymphomatoid granulomatosis (LG) is Epstein-Barr virus associated, a rare aggressive B cell lymphoproliferative disease. The most common sites of involvement are lungs, skin, kidneys, liver and central nervous system. The clinical presentation of pulmonary LG can mimic infectious diseases, malignancies or vasculitis. While treatment approach of low grade disease is watch and wait, patients with advanced stage   require aggressive treatment with chemotherapy. Patients with hematological malignancy as well as solid tumors are at increased risk of venous thromboembolic events (VTE). We reported here in a case of pulmonary LG who was complicated with VTE during treatment with chemo-immunotherapy After 4 cycles of R-CHOP, she achieved complete remission for LG and was followed up without relapse for 2 years. She was anticoagulated with Low-Molecular-Weight Heparin (LMWH) during chemotherapy period, and the thrombus improved over the next several weeks. While on this paper written patient was pregnant with 10 weeks.